Effect of pressure cycling on iron: Signatures of an electronic instability and unconventional superconductivity - Yadav, C. S. (2013)
High pressure electrical resistivity and x-ray diffraction experiments have been performed on Fe single crystals. The crystallographic investigation provides direct evidence that in the martensitic bcc → hcp transition at 14 GPa the {110}bcc become the {002}hcp directions. During a pressure cycle, resistivity shows a broad hysteresis of 6.5 GPa, whereas superconductivity, observed between 13 and 31 GPa, remains unaffected. Upon increasing pressure an electronic instability, probably a quantum critical point, is observed at around 19 GPa and, close to this pressure, the superconducting Tc and the isothermal resistivity (0 <T < 300 K) attain maximum values. In the superconducting pressure domain, the exponent n = 5/3 of the temperature power law of resistivity and its prefactor, which mimics Tc, indicate that ferromagnetic fluctuations may provide the glue for the Cooper pairs, yielding unconventional superconductivity.